THE TAXATION OF ELECTRONIC COMMERCE AS SPONSOR OF BASIC INCOME: COMPENSATING SOCIAL INEQUALITIES IN THE CONTEXT OF BRAZILIAN AUSTERITY POLICY - Bruno da Silva , Alexandre Antônio; da Silva Bezerra, Stéfani Clara (Revista Inclusiones, 2021)
The situation of socioeconomic vulnerability in the context of the pandemic by COVID-19 resumed the discourse on basic income. In a scenario of financial recession, Brazil does not seem to have the resources to pay for this assistance policy. With a bibliographic and quantitative research, the work seeks to analyze the proposal for the taxation of electronic commerce as a potential sponsor of basic income, since it is presented as a measure capable of compensating for the social inequalities aggravated by the Austerity Policy. It was noted that, despite the legislative initiatives, the taxation of electronic commerce is not something simple, but it involves a wide range of services and technological products that do not contain a legal provision and fall in normative lagoons. The Tax Reform seems right to unify taxation by using electronic commerce, but there is something to be desired when it is restricted to federal taxes and because it does not present a hypothesis of clear impact.